Multidrug-resistant Gram-negative bacteria in lung transplantation: a narrative review of infectious complications and current management - Sambo, Margherita; Giuliano, Gabriele; Bennett, David; Luzzi, Luca; Franchi, Federico; Tumbarello, Mario; Montagnani, Francesca (Frontiers in Microbiology, 2025)
Multidrug-resistant Gram-negative bacterial (MDR-GNB) infections represent a major challenge in lung transplantation (LuTx), due to their possible association with poor clinical outcomes and the limited availability of effective antimicrobial agents. Nevertheless, MDR-GNB colonization or infection is no longer considered an absolute contraindication to transplantation. Recent recommendations issued by leading societies in clinical microbiology and infectious diseases, national expert groups, and transplant medicine professionals provide updated recommendations on antimicrobial strategies, encompassing both established and newly approved agents. Following an overview of the epidemiology of infections in LuTx recipients, with a focus on the specific impact of MDR-GNB, this review aims to explore current evidence on diagnostic approaches, prophylactic measures, and therapeutic management. Remaining knowledge gaps in this area are also highlighted, emphasizing the need for further research to optimize prevention and treatment strategies in this high-risk population.